Establishing a biblical seminary of the Philippines Institutional Archives - Cruz, Luis Ezra D. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
The purpose of the project is to establish a formal, working, and sustainable Biblical Seminary of the Philippines (BSOP) International Archives. By the ensuring that materials with lasting value to the organization archives, the BSOP's institutional identity and memory shall be preserved and be made available to its community.